N-nitrosomelatonin - Turjanski, A. (2000)
The title compound, N-[2-(5-methoxy-1-nitroso-1H-indol-3-yl)ethyl]acetamide, C13H15N3O3, an N-nitroso derivative of melatonin, crystallizes in the monoclinic C2/c space group. The molecules are arranged in such a way that the aromatic rings are in a planar conformation, with the alkylamide side chains in a different plane, at a dihedral angle of 108.60 (6)°. The alkylamide chains are interconnected by hydrogen bonds, constituting an infinite array.